Analisis Kadar Siklamat Pada Selai Yang Beredar Di Perumahan BTP Kota Makassar Dengan Metode Spektrofotometri UV-Vis - Andini, Ayu; Widiastuti, Harti; Baits, Muzakkir (PHARMACY UMI JOURNAL SYSTEM, 2024)
Sweeteners are chemical compounds that are widely added and used in various processed food and beverage products, one of which is jam. Jam is a semi-solid food made from fruit or other processed products. Sweeteners consist of natural sweeteners and artificial sweeteners. Cyclamate is one of the artificial sweeteners that is often used in society because it has a sweetness intensity 30 times that of pure sugar. Excessive use of cyclamate can cause negative effects on health such as cancer (carcinogenic), nerve disorders, impaired liver function, stomach irritation and changes in cell function. The maximum limit for using cyclamate in jam according to SNI 01-0222-1995 is 2 g/kg. This study aims to identify and determine the levels of cyclamate in jam circulating in BTP Makassar housing. The type of research used is laboratory observation with simple random sampling technique. This research was conducted qualitatively (TLC and precipitation method) and quantitatively (uv-vis spectrophotometric method). The results of this study indicated that all negative samples contained cyclamate with a standard Rf value of 0.875 for cyclamate.